Supporting the local decision-making process in England in the context of integrated care - Gongora Salazar, P (2024)
Over the last decade, England has emphasised the implementation of new care models and restructured the local commissioning architecture aiming to strengthen its integration agenda. Although this overhaul has increased the need for evidence-based decisions, research suggests that local commissioners may not have enough evidence to make well-informed investment decisions. Evaluating these models systematically and empirically can be challenging, and traditional economic evaluation methods may not be suitable. This thesis develops a relevant, practical and theoretically sound decision-support framework, based on multi-criteria decision analysis (MCDA) for evaluating and monitoring new models of care at local level in England. The framework’s structure was informed by semi-structured interviews with local stakeholders and a systematic literature review on the application of MCDA in healthcare. Public preferences were integrated through a discrete choice experiment (DCE) with the general public. The framework's feasibility was tested on two early intervention in psychosis (EIP) services using electronic health record data. The interviews highlighted the importance of rational and transparent local commissioning processes. Through the interviews and literature review, a comprehensive set of value-based elements was identified that can be objectively applied to assess new models of care. Results of the DCE suggest that the public assigns high importance to elements of value that are not captured in conventional value metrics. The EIP evaluation demonstrated the framework's feasibility in mental health, a key priority area for NHS England. The DCE and service evaluation emphasised the importance of reporting the MCDA total score with and without the cost criterion. The proposed decision-support framework has the potential to assist decision-makers in strengthening the local commissioning process for integrated care. Although further exploration is required to determine its broader applicability and effectiveness, the proposed framework establishes a basis to enhance local population health management in England, underpinned by real-world evidence.